(untitled) (Journal of Foreign Language Studies, 2024)
This study set its goal to detect how each strategy influences students’ listening comprehension when it is applied to their tasks and to find out students’ perceptions of the application of note-taking strategies in different legal English listening tasks. An explanatory mixed methods design involving two instruments, including a questionnaire and semi-structured interviews, was conducted. 175 students taking legal English courses completed the questionnaire. After collecting the numeric data, interviews with open-ended questions were conducted with 20 participants. The findings provided helpful information regarding how notetaking strategies affect students’ listening comprehension when they are applied to different Legal English tasks. Besides, two recommendations for future studies were proposed, focusing on the variable of proficiency level and the relationship between effective note-taking and task fulfillment.